Effect of Diabetes Mellitus Type 2 on the Correlation of Vitamin D with Lipid Profile in Iraqi Patients - Abu-Shana, Jinan Hameed; Abdulkareem, Nadia Ghassan; Jasim, Ahmed Obaid; Abbood, Yasameen Hussein (Iraqi Journal of Science, 2024)
Vitamin D deficiency has been linked to several conditions, including type 2 diabetes. The purpose of this study is to determine if there is an effect of type 2 diabetes on the association between vitamin D level, glycemic indices, and lipid profiles. The study was conducted at Al-Noamman Hospital, included 257 patients with type 2 diabetes and 40 healthy participants of both sexes with matching ages ranging from 26 to 80 years. The lipid profile, postprandial glucose (PPG), HbA1C, and serum vitamin D were measured. The results showed that 89 (34.6%) of diabetics have vitamin D insufficiency (less than 30 ng/mL). 155 diabetic patients (uncontrolled glycemic) with elevated HbA1C (9.07% ± 2.5), and from those, about 33.5% have vitamin D insufficiency; they are of age ≥ 55 years, 58.1% female, and 41.9% male, and they have a significant correlation (r = 0.17, P < 0.05) between HbA1C and vitamin D. All diabetic patients who are classified according to HbA1C subgroups have highly significant correlations (P < 0.01) among age and vitamin D; cholesterol with VLDL and LDL; and TG with VLDL. In controlled diabetes patients (HbA1C ˂ 5.7%), a highly significant correlation was found between HDL and vitamin D (r = 0.50, P ˂ 0.01(. We conclude that vitamin D level is highly significantly related to age and sex in diabetic patients who displayed highly significant dyslipidemia and were associated with 34.6% vitamin D insufficiency (significantly with uncontrolled diabetes mellitus patients).